Association between intraocular pressure and loss of visual field in chronic simple glaucoma. Issue 1 (January 1990) - Vogel, R; Crick, R P; Newson, R B; Shipley, M; Blackmore, H; Bulpitt, C J
Abstract : This paper reports the analyses on data from 747 patients with chronic simple glaucoma (CSG) recorded in the King's College Hospital glaucoma data base between January 1970 and February 1985, having a mean follow-up time of 5.1 years (mode 8 years) with the object of determining the relationship of intraocular pressure (IOP) and visual field loss in CSG. A highly significant negative relationship was found between the presenting visual field coefficient (FC) and the untreated IOP (r = -0.26, p = 0.0001) - that is, the higher the IOP on detection, the worse is the visual field. A weak negative correlation was present between the change of FC per year and the treated IOP (r = -0.06), p = less than 0.05). At treated IOPs less than or equal to 18 mmHg visual field loss averaged 0.6 unit per year and for IOPs greater than 18 mmHg the average loss was 1.2 units per year. The data confirm both the importance of a raised IOP in the causation of chronic glaucomatous visual field loss and the importance of reducing the IOP in patients with chronic simple glaucoma.